Analysis of Customer Bonding Implementation Strategy on Membership Loyalty of Parkson Centro Card at Centro Department Store the Plaza Semanggi - Rohmandiyas, Nanang Agung (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the customer bonding carried out by the Centro Department Store at The Plaza Semanggi and determine customer loyalty and the effect of customer bonding on the commitment of Parkson Centro Card members. This research is correlational quantitative research. The population in this study are customers from the Cetro Department Store at The Plaza Semanggi who are registered as members of the Parkson Centro Card for at least 1 year. The samples taken in this study were 100 peoples. The variables of this research are customer bonding and customer loyalty. The data collection method in this study uses a customer bonding scale and a customer loyalty scale. The method of data analysis in this study used regression analysis.